Polyvinyl alcohol-keratin semi-interpenetrating network hydrogel as well as preparation method and application thereof
By mixing keratin with molecular weight greater than 2kDa with polyvinyl alcohol and metal salts, a semi-interpenetrating network hydrogel is formed, and the gel structure is regulated by endogenous addition of cations, the problems of ion permeability and hydrogen bond stability in the prior art are solved, and the preparation of high-performance hydrogels is realized, which is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411891551.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, keratin-polyvinyl alcohol hydrogels have uneven ion penetration, excessive or insufficient interaction between ions and gels, exogenous cationic liquid immersion destroys the hydrogen bond stability of PVA frozen-thaw gels, and the molecular weight of small molecule hydrolyzed keratin is usually less than 2kDa, limiting its application in high-performance hydrogels.
Keratin with a molecular weight greater than 2kDa is mixed with polyvinyl alcohol and metal salt, and a semi-interpenetrating network hydrogel is formed through frozen and melting treatment. By adding cations to the endogenously, metal ions are used to regulate the network structure and interaction of the gel to optimize the mechanical properties and stability of the gel.
The mechanical properties, moisture control ability and stability of polyvinyl alcohol-keratin semi-interpenetrating network hydrogels have been improved, and the problems of uneven ion penetration and hydrogen bond stability in the prior art are overcome. They are suitable for the preparation of biomedical materials, food packaging materials and flexible electronic components.
Smart Images

Figure CN119708541A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gel materials, and particularly relates to a polyvinyl alcohol-keratin semi-interpenetrating network hydrogel and a preparation method and application thereof. Background Art
[0002] A large amount of waste is generated during the slaughtering process of poultry, including feathers, eggshells and nails, among which feathers are one of the main wastes in the poultry farming industry chain. Keratin is an important structural protein present in vertebrate epithelial cells, belonging to the intermediate filament protein superfamily, accounting for about 91% of the total composition of feathers. Keratin is rarely used alone except as a dietary supplement in its hydrolyzed form, and is mostly used to prepare keratin-based materials. Keratin-based materials have good biodegradability, biocompatibility and mechanical durability. In particular, the application of keratin hydrogels in biomedicine has been relatively mature, including wound repair, drug delivery, bone enhancement and nerve regeneration.
[0003] Although keratin hydrogels of pure or modified proteins have the advantages of simple synthesis process, diverse modifications, uniform network structure and good biocompatibility, the single protein network limits the stability and mechanical strength of keratin hydrogels. Therefore, improving the mechanical properties of keratin hydrogels by adding polymers to keratin hydrogels to form mixed hydrogels (i.e., protein-polymer hydrogels) is an effective way to increase the breadth of keratin applications. Polyvinyl alcohol (PVA) is a hydrophilic, biodegradable and biocompatible synthetic polymer that can produce phase separation through repeated freezing and thawing, thereby forming crystalline clusters as cross-linking points. At present, various types of hydrogels based on proteins and PVA have been widely studied, and PVA has been fully recognized as a polymer matrix for natural protein hydrogels.
[0004] It can be seen that the current research on keratin-polyvinyl alcohol hydrogels is relatively mature. Most of the existing literature on the effect of salt ions on PVA freeze-thaw cycle gels tends to exogenously soak cationic liquids after gel formation to change the hydration of the gel, redistribute the water, and then change the hydrophilicity or hydrophobicity of the gel. However, there are the following problems when using exogenous cationic liquids: a. The gel may absorb or lose water excessively, affecting its functionality; b. Some ions only interact on the surface of the gel and cannot effectively penetrate into the deep area, resulting in uneven gel performance; c. The gel structure after freeze-thaw cycles is unstable, and exogenous ions may destroy the intermolecular / intermolecular forces of freeze-thaw cycle gels, affecting the stability of the gel. In addition, current research focuses on small molecule hydrolyzed keratin, whose molecular weight is usually less than 2kDa, which limits its application in high-performance hydrogels. Summary of the invention
[0005] In view of the deficiencies in the above-mentioned prior art, the present invention provides a polyvinyl alcohol-keratin semi-interpenetrating network hydrogel and a preparation method and application thereof. The present invention uses keratin with a molecular weight greater than 2 kDa as a raw material, adds a metal salt to a PVA-keratin mixed solution, promotes the stable arrangement of the crystal phase structure and the nanostructure, and makes the nanostructure arrangement of the metal ions more orderly, thereby overcoming the problems of uneven ion penetration, excessive or insufficient interaction between ions and gel, and destruction of the hydrogen bond stability of the PVA freeze-thaw gel by immersion in an exogenous cationic liquid in the protein-polyvinyl alcohol hydrogel in the prior art, optimizing the network structure of the gel and the recovery ability after freeze-thaw cycles, and overcoming the technical defect of gel structure degradation caused by immersion in an exogenous cationic liquid in the prior art.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] The preparation method of polyvinyl alcohol-keratin semi-interpenetrating network hydrogel comprises the following steps:
[0008] After the aqueous solution of keratin aggregates is mixed with the aqueous solution of polyvinyl alcohol, a metal salt is added to obtain a PVA-keratin mixed solution.
[0009] Wherein, the metal salt is selected from soluble sodium salt, soluble calcium salt or soluble aluminum salt.
[0010] Wherein, the metal salt is selected from soluble sodium salt, soluble calcium salt or soluble aluminum salt; when the metal salt is selected from soluble sodium salt, the concentration of soluble sodium salt in the PVA-keratin mixed solution is 0<c≤0.2mol / L, when the metal salt is selected from soluble calcium salt, the concentration of soluble calcium salt in the PVA-keratin mixed solution is 0<c≤0.1mol / L, when the metal salt is selected from soluble aluminum salt, the concentration of soluble aluminum salt in the PVA-keratin mixed solution is 0<c≤0.1mol / L.
[0011] The PVA-keratin mixed solution is frozen and thawed, so that the polyvinyl alcohol forms a network gel structure and changes from liquid to solid, thereby obtaining a polyvinyl alcohol-keratin semi-interpenetrating network hydrogel.
[0012] After adding metal salts, the mechanical properties of PVA-keratin hydrogels are significantly affected, as shown in the following:
[0013] Enhancement: Low concentrations of metal salts (such as Na + ) can promote the orderly arrangement of the network structure and enhance the mechanical properties of PVA-keratin semi-IPN hydrogel. 2+ 、Al 3+) at high concentrations will lead to excessive cross-linking or electrostatic shielding, destroying the network of PVA-Keratin semi-IPN hydrogel, causing the rigidity and strength of PVA-Keratin semi-IPN hydrogel to decrease, and even causing it to lose its molding ability. 2+ When the concentration exceeded 0.15 mol / L, the excessive cross-linking caused by the calcium bridge effect significantly reduced the viscoelasticity of the gel. 3+ The strong electrostatic shielding effect directly leads to the collapse of the gel network structure.
[0014] Ion doping has an important influence on the preparation of macromolecular gels. Its mechanism of action includes: a. Regulating intermolecular interactions: Ions regulate the interaction between PVA and feather keratin molecules through electrostatic shielding, ion bridge action or ion induction, such as Ca 2+ The calcium bridge effect of Na enhances the cross-linking strength of PVA and feather keratin, but too high a concentration may cause the network to be over-cross-linked and lose elasticity. b. Promote the formation of network structure: Low concentration of Na + Ions can reduce the negative charge repulsion in the system, promote the uniform distribution and network formation of PVA and feather keratin, and thus help the embedding and shaping of macromolecules. c. Destroy the molecular network: Highly charged ions (such as Al 3+ ) will seriously damage the molecular network and cause the gel to fail to form, which shows that excessive ionic interference is harmful to the preparation of macromolecular gels.
[0015] Preferably, the keratin is selected from feather keratin or wool keratin, and has a molecular weight greater than 2 kDa.
[0016] Preferably, in the polyvinyl alcohol-keratin semi-IPN hydrogel, the mass percentage of keratin aggregates is 1-4wt%.
[0017] Preferably, in the polyvinyl alcohol-keratin semi-IPN hydrogel, the mass percentage of polyvinyl alcohol is 14-16 wt %.
[0018] Preferably, in the polyvinyl alcohol-keratin semi-IPN hydrogel, the concentration of the metal salt is 0.05-0.2 mol / L.
[0019] Preferably, the mixture is first frozen at -18 to -22°C for 22 hours and then thawed at 20 to 30°C for 2 hours.
[0020] Preferably, feathers are used as raw materials and keratin in feathers is extracted by microwave-assisted L-cysteine method. The optimal conditions for extracting keratin in feathers by microwave-assisted L-cysteine method are: L-cysteine concentration 15 g / L, pH value 12, microwave power 400 W, microwave time 10 min, temperature 90° C.; the optimal pH value for keratin preparation is 2, heating temperature 90° C., and heating time 6 h.
[0021] The invention also protects the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel prepared by the preparation method.
[0022] The present invention also protects the application of the above-mentioned polyvinyl alcohol-keratin semi-interpenetrating network hydrogel in the preparation of biomedical materials. Both feather keratin and PVA have good biocompatibility. The present invention adopts a cyclic freeze-thaw method to prepare the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel, which is a physical cross-linking method without any excess chemical cross-linking agent, so the obtained polyvinyl alcohol-keratin semi-interpenetrating network hydrogel will not cause damage to the human body.
[0023] The present invention also protects the application of the above-mentioned polyvinyl alcohol-keratin semi-interpenetrating network hydrogel in the preparation of food packaging materials. The polyvinyl alcohol-keratin semi-interpenetrating network hydrogel obtained by the method of the present invention has excellent mechanical properties, biodegradability and food safety. Its moisture regulation ability and adjustable microstructure are suitable for absorbing excess moisture and delaying food oxidation and deterioration. At the same time, polyvinyl alcohol and feather keratin are renewable and environmentally friendly, and have good application and promotion value.
[0024] The present invention also protects the use of the above-mentioned polyvinyl alcohol-keratin semi-interpenetrating network hydrogel in the preparation of flexible electronic components. The polyvinyl alcohol-keratin semi-interpenetrating network hydrogel obtained by the method of the present invention has the following advantages: a. Excellent mechanical properties: The high toughness and adjustable elasticity of the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel meet the requirements of flexible electronic devices for mechanical durability and deformation ability; b. Excellent conductivity: Through ion doping (such as Na + , Ca 2+ ), polyvinyl alcohol-keratin semi-interpenetrating network hydrogel has ionic conductivity and can be used as a conductive layer or ionic conductor for flexible electronic components; c. Environmental friendliness and biocompatibility: The natural source and biocompatibility of feather keratin make it suitable for wearable devices or biosensors, reducing the negative impact on the human body and the environment; d. Humidity and temperature responsiveness: polyvinyl alcohol-keratin semi-interpenetrating network hydrogel is sensitive to humidity and temperature, and can realize the signal response of flexible sensors in different environments; e. Microstructure adjustability: The pore structure of polyvinyl alcohol-keratin semi-interpenetrating network hydrogel is easy to control, and nanomaterials (such as metal particles or carbon nanotubes) can be embedded to further enhance the electrical properties.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention uses keratin with a molecular weight greater than 2kDa as a raw material, mixes keratin aggregates, polyvinyl alcohol and metal salts, and then freezes and thaws to obtain polyvinyl alcohol-keratin semi-interpenetrating network hydrogel. The present invention uses metal ions to regulate the network structure of polyvinyl alcohol-keratin semi-interpenetrating network hydrogel and its related physical and chemical properties, including mechanical properties (rigidity, toughness), moisture regulation ability (ratio of bound water to free water), intermolecular interactions and gel stability by adding cations of different types and concentrations (such as Na + , Ca 2+ 、Al 3+ ) uses ions to interact with functional groups (such as hydroxyl groups, amino groups, and disulfide bonds) in the PVA-keratin mixed solution to produce electrostatic shielding, ion bridge effects, or charge induction effects, thereby changing the crosslinking pattern, molecular arrangement, and internal pore structure of the gel.
[0027] The results of metal ion regulation are as follows: a. Mechanical properties: low-charge ions (Na + ) or low concentrations of highly charged ions (Ca 2+ or Al 3+ ) Enhance the rigidity and strength of polyvinyl alcohol-keratin semi-interpenetrating network hydrogel and improve the mechanical stability. b. Moisture regulation: polyvinyl alcohol-keratin semi-interpenetrating network hydrogel has humidity control performance. c. Structural stability: ion concentration and type change the cross-linking degree and pore structure of polyvinyl alcohol-keratin semi-interpenetrating network hydrogel through electrostatic shielding and ion bridge effect mechanism. Na + or low concentrations of highly charged ions (Ca 2+ or Al 3+ ) can promote the ordering and densification of the gel network and enhance its stability. Appropriate ion doping promotes network uniformity and improves the physical and chemical stability of the gel. d. Performance adjustability: According to different application requirements, the optimization of specific performance can be achieved by regulating the type and concentration of ions to meet the diverse needs of food packaging or flexible electronic components. e. The endogenous cation addition method allows the ions to fully react with polyvinyl alcohol and protein before the gel is formed, greatly enhancing the stability of the gel after freeze-thaw cycles and avoiding performance degradation caused by the loss of ions in the later stage.
[0028] 2. In the present invention, different ions are used to interact with the functional groups of the PVA-keratin mixed solution, which significantly regulates the network structure of the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel and improves its physical and chemical properties. The physical properties are mainly reflected in the mechanical properties and nanostructure stability, and the chemical properties are mainly reflected in the intermolecular interaction and molecular structure stability. By using a single metal type of multivalent metal ions to form metal-coordination bonds or complexes with the PVA-keratin mixed solution, the crosslinking degree of the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel is regulated. Different metal ions (such as Na + , Ca 2 + 、Al 3+ ) on the polyvinyl alcohol-keratin semi-IPN hydrogel is mainly reflected in the regulation of network structure, intermolecular interaction and water distribution. The performance is reflected in the regulation of mechanical properties, water absorption capacity and water distribution, which in turn affects the strength, elasticity, water retention capacity and stability of the gel.
[0029] 3. The present invention uses a semi-interpenetrating network hydrogel of polyvinyl alcohol and feather keratin to reveal the mechanism of keratin concentration and ionic environment on the regulation of hydrogel properties. This study not only promotes the application of keratin-based hydrogels in a wider range of fields, but also provides a theoretical basis and reference for future practical applications in biomedicine and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The EDS images of PVA of Comparative Example 5, HyK of Comparative Example 6, HK of Comparative Example 1, NaK of Example 1, CaK of Example 5, and AlK of Example 7, and the SEM images at 1000 times and 10000 times.
[0031] Figure 2 In the figure, Figure A and Figure D are both frequency scanning diagrams of the gel of Comparative Example 1-5, Figure B and Figure E are both frequency scanning diagrams of the gel of Example 1-4, Figure C and Figure F are both frequency scanning diagrams of the gel of Example 5-6 and Comparative Example 7-8, and Figure G is a power law equation fitting result diagram of the gel of Example 1-6, Comparative Example 1-5 and Comparative Example 7-8.
[0032] Figure 3 The graph is a graph of gel hardness of Examples 1-6 and Comparative Examples 1-5.
[0033] Figure 4 It is a graph of the solvent holding capacity of PVA of Comparative Example 5, HyK of Comparative Example 6, HK of Comparative Example 1, NaK of Example 1 and CaK of Example 5.
[0034] Figure 5It is a DSC curve chart of PVA of Comparative Example 5, HyK of Comparative Example 6, HK of Comparative Example 1, NaK of Example 1, CaK of Example 5 and AlK of Example 7.
[0035] Figure 6 In the figure, A is a low-field NMR scan of the gel of comparative example 1-5; B is a low-field NMR scan of the gel of embodiment 1-4; C is a low-field NMR scan of the gel of embodiment 5-6 and comparative example 7-8; D is a table of the proportions of different types of water after fitting of the gels of embodiments 1-6, comparative examples 1-5 and comparative examples 7-8.
[0036] Figure 7 The Raman spectra of PVA of Comparative Example 5, HyK of Comparative Example 6, HK of Comparative Example 1, NaK of Example 1, CaK of Example 5, and AlK of Example 7 are shown.
[0037] Figure 8 1 and 2 are XRD diagrams of PVA of Comparative Example 5, HyK of Comparative Example 6, HK of Comparative Example 1, NaK of Example 1, CaK of Example 5, and AlK of Example 7.
[0038] Fig. 9 SAXS1D diagrams of PVA of Comparative Example 5, HyK of Comparative Example 6, HK of Comparative Example 1, NaK of Example 1, CaK of Example 5, and AlK of Example 7.
[0039] Fig.10 The SAXS curves of PVA of Comparative Example 5, HyK of Comparative Example 6, HK of Comparative Example 1, NaK of Example 1, CaK of Example 5 and AlK of Example 7 are shown in FIG. Beaucage uniform model fit plot for intervals. DETAILED DESCRIPTION
[0040] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0041] Current research on keratin-polyvinyl alcohol hydrogels is mostly focused on small molecule hydrolyzed keratin. The molecular weight of small molecule hydrolyzed keratin is usually less than 2kDa. The limitations are mainly reflected in the following points: a. Molecular compatibility and cross-linking mode: small molecules are easier to form a uniform network with the PVA substrate due to their low molecular weight and simple structure, while large molecules are difficult to effectively embed into the PVA network due to their size and molecular chain flexibility; b. Solubility and dispersibility: The solubility and dispersibility of large molecular keratin in aqueous solution are poor, which limits its uniform mixing and network formation with PVA.
[0042] The present invention improves the compatibility of keratin and PVA by screening keratin, thereby enhancing the embedding ability of keratin in PVA. At the same time, the natural disulfide bonds and amino acid residues of keratin provide more cross-linking sites, thereby helping to form a more stable semi-interpenetrating network structure and realize the preparation of macromolecular gel.
[0043] The technical solution of the present invention is studied using embodiments and comparative examples below, and the specific research methods and results are as follows:
[0044] Example 1
[0045] The preparation method of polyvinyl alcohol-keratin semi-interpenetrating network hydrogel comprises the following steps:
[0046] S1. Wash and chop 20g of white-feather chicken feathers, add them to 1L of keratin extract containing 15g of L-cysteine, microwave them for 10min at a microwave power of 400W and a temperature of 90°C, pour them into a dialysis bag and dialyze them with deionized water for three days. The molecular weight cutoff of the dialysis bag is 8K-14KDa to obtain a pure keratin solution.
[0047] S2. Use 1 mol / L HCl solution to adjust the pH of 10 mg / mL keratin solution to 2.0, heat it in a water bath at 90° C. for 6 h, obtain keratin aggregates, freeze-dry them, and set aside.
[0048] S3. Mix the keratin aggregates in water, and adjust the pH to 7.2 with a 2 mol / L NaOH solution to obtain a keratin aggregate solution with a mass percentage of 5 wt%.
[0049] S4. PVA was mixed with water, and stirred in a 90° C. water bath for 3 h to ensure that the PVA was fully dissolved, thereby obtaining a PVA solution with a mass percentage of 30 wt %.
[0050] S5, after mixing the keratin aggregate solution and the PVA solution, stirring at 50°C for 3h, adding 2mol / L NaCl solution, so that the mass percentage of keratin aggregates in the system is 2wt%, the mass percentage of PVA is 15wt%, and the mass percentage of NaCl is 2mol / L. +The concentration is 0.1 mol / L to obtain a PVA-keratin mixed solution.
[0051] S6. The PVA-keratin mixed solution was first frozen at -20°C for 22 hours, then thawed at 25°C for 2 hours, and the freezing and thawing cycle was repeated three times to obtain a polyvinyl alcohol-keratin semi-IPN hydrogel, which was recorded as NaK or 0.1Na or 0.1N.
[0052] Example 2
[0053] The preparation method of polyvinyl alcohol-keratin semi-IPN hydrogel is the same as the preparation steps of Example 1, except that NaCl is replaced from 2 mol / L to 1 mol / L, and the ion addition amount is 0.05 mol / L, recorded as 0.05Na or 0.05N.
[0054] Example 3
[0055] The preparation method of polyvinyl alcohol-keratin semi-IPN hydrogel is the same as the preparation steps of Example 1, except that NaCl is replaced from 2 mol / L to 3 mol / L, and the ion addition amount is 0.15 mol / L, recorded as 0.15Na or 0.15N.
[0056] Example 4
[0057] The preparation method of polyvinyl alcohol-keratin semi-IPN hydrogel is the same as the preparation steps of Example 1, except that NaCl is replaced from 2 mol / L to 4 mol / L, and the ion addition amount is 0.2 mol / L, recorded as 0.2Na or 0.2N.
[0058] Example 5
[0059] The preparation method of polyvinyl alcohol-keratin semi-interpenetrating network hydrogel comprises the following steps:
[0060] S1. Wash and chop 20g of white-feather chicken feathers, add them to 1L of keratin extract containing 15g of L-cysteine, microwave them for 10min at a microwave power of 400W and a temperature of 90°C, pour them into a dialysis bag and dialyze them with deionized water for three days. The molecular weight cutoff of the dialysis bag is 8K-14KDa to obtain a pure keratin solution.
[0061] S2. Use 1 mol / L HCl solution to adjust the pH of 10 mg / mL keratin solution to 2.0, heat it in a water bath at 90° C. for 6 h, obtain keratin aggregates, freeze-dry them, and set aside.
[0062] S3. Mix the keratin aggregates in water, and adjust the pH to 7.2 with a 2 mol / L NaOH solution to obtain a keratin aggregate solution with a mass percentage of 5 wt%.
[0063] S4. PVA was mixed with water, and stirred in a 90° C. water bath for 3 h to ensure that the PVA was fully dissolved, thereby obtaining a PVA solution with a mass percentage of 30 wt %.
[0064] S5. After mixing the keratin aggregate solution and the PVA solution, stir at 50°C for 3h, and then add 2mol / L CaCl2 solution to make the mass percentage of keratin aggregates in the system 2wt%, the mass percentage of PVA 15wt%, and the mass percentage of CaCl2 15wt%. 2+ The concentration is 0.1 mol / L to obtain a PVA-keratin mixed solution.
[0065] S6. The PVA-keratin mixed solution was first frozen at -20°C for 22 hours, then thawed at 25°C for 2 hours, and the freezing and thawing cycle was repeated three times to obtain a polyvinyl alcohol-keratin semi-interpenetrating network hydrogel, which was recorded as CaK or 0.1Ca or 0.1C.
[0066] Example 6
[0067] The preparation method of polyvinyl alcohol-keratin semi-IPN hydrogel is the same as the preparation steps of Example 5, except that CaCl2 is replaced from 2 mol / L to 1 mol / L. At this time, the ion addition amount is 0.05 mol / L, recorded as 0.05Ca or 0.05C.
[0068] Example 7
[0069] The preparation method of polyvinyl alcohol-keratin semi-interpenetrating network hydrogel comprises the following steps:
[0070] S1. Wash and chop 20g of white-feather chicken feathers, add them to 1L of keratin extract containing 15g of L-cysteine, microwave them for 10min at a microwave power of 400W and a temperature of 90°C, pour them into a dialysis bag and dialyze them with deionized water for three days. The molecular weight cutoff of the dialysis bag is 8K-14KDa to obtain a pure keratin solution.
[0071] S2. Use 1 mol / L HCl solution to adjust the pH of 10 mg / mL keratin solution to 2.0, heat it in a water bath at 90° C. for 6 h, obtain keratin aggregates, freeze-dry them, and set aside.
[0072] S3. Mix the keratin aggregates in water, and adjust the pH to 7.2 with a 2 mol / L NaOH solution to obtain a keratin aggregate solution with a mass percentage of 5 wt%.
[0073] S4. PVA was mixed with water, and stirred in a 90° C. water bath for 3 h to ensure that the PVA was fully dissolved, thereby obtaining a PVA solution with a mass percentage of 30 wt %.
[0074] S5, after mixing the keratin aggregate solution and the PVA solution, stirring at 50°C for 3h, adding 2mol / L AlCl3 solution, so that the mass percentage of keratin aggregates in the system is 2wt%, the mass percentage of PVA is 15wt%, and the mass percentage of AlCl3 is 2mol / L. 3+ The concentration is 0.1 mol / L to obtain a PVA-keratin mixed solution.
[0075] S6. The PVA-keratin mixed solution was first frozen at -20°C for 22 hours, and then thawed at 25°C for 2 hours, and the freezing and thawing cycle was repeated three times to obtain a polyvinyl alcohol-keratin semi-interpenetrating network hydrogel, denoted as AlK.
[0076] Example 8
[0077] The preparation method of polyvinyl alcohol-keratin semi-interpenetrating network hydrogel comprises the following steps:
[0078] S1. Wash and chop 20g of white-feather chicken feathers, add them to 1L of keratin extract containing 15g of L-cysteine, microwave them for 10min at a microwave power of 400W and a temperature of 90°C, pour them into a dialysis bag and dialyze them with deionized water for three days. The molecular weight cutoff of the dialysis bag is 8K-14KDa to obtain a pure keratin solution.
[0079] S2. Use 1 mol / L HCl solution to adjust the pH of 10 mg / mL keratin solution to 2.0, heat it in a water bath at 90° C. for 6 h, obtain keratin aggregates, freeze-dry them, and set aside.
[0080] S3. Mix the keratin aggregates in water, and adjust the pH to 7.2 with a 2 mol / L NaOH solution to obtain a keratin aggregate solution with a mass percentage of 2.5 wt%.
[0081] S4. PVA was mixed with water, and stirred in a 90° C. water bath for 3 h to ensure that the PVA was fully dissolved, thereby obtaining a PVA solution with a mass percentage of 30 wt %.
[0082] S5, after mixing the keratin aggregate solution and the PVA solution, stirring at 50°C for 3h, adding 2mol / L NaCl solution, so that the mass percentage of keratin aggregates in the system is 1wt%, the mass percentage of PVA is 14wt%, and the mass percentage of NaCl is 1. + The concentration is 0.1 mol / L to obtain a PVA-keratin mixed solution.
[0083] S6. The PVA-keratin mixed solution was first frozen at -18°C for 22 hours, then thawed at 30°C for 2 hours, and the freeze-thaw cycle was repeated three times to obtain a polyvinyl alcohol-keratin semi-interpenetrating network hydrogel.
[0084] Example 9
[0085] The preparation method of polyvinyl alcohol-keratin semi-interpenetrating network hydrogel comprises the following steps:
[0086] S1. Wash and chop 20g of white-feather chicken feathers, add them to 1L of keratin extract containing 15g of L-cysteine, microwave them for 10min at a microwave power of 400W and a temperature of 90°C, pour them into a dialysis bag and dialyze them with deionized water for three days. The molecular weight cutoff of the dialysis bag is 8K-14KDa to obtain a pure keratin solution.
[0087] S2. Use 1 mol / L HCl solution to adjust the pH of 10 mg / mL keratin solution to 2.0, heat it in a water bath at 90° C. for 6 h, obtain keratin aggregates, freeze-dry them, and set aside.
[0088] S3. Mix the keratin aggregates in water, and adjust the pH to 7.2 with a 2 mol / L NaOH solution to obtain a keratin aggregate solution with a mass percentage of 10 wt%.
[0089] S4. PVA was mixed with water, and stirred in a 90° C. water bath for 3 h to ensure that the PVA was fully dissolved, thereby obtaining a PVA solution with a mass percentage of 30 wt %.
[0090] S5, after mixing the keratin aggregate solution and the PVA solution, stirring at 50°C for 3h, adding 2mol / L NaCl solution, so that the mass percentage of keratin aggregates in the system is 4wt%, the mass percentage of PVA is 16wt%, and the mass percentage of NaCl is 1. + The concentration is 0.1 mol / L to obtain a PVA-keratin mixed solution.
[0091] S6. The PVA-keratin mixed solution was first frozen at -22°C for 22 hours, then thawed at 20°C for 2 hours, and the freeze-thaw cycle was repeated three times to obtain a polyvinyl alcohol-keratin semi-interpenetrating network hydrogel.
[0092] Comparative Example 1
[0093] The preparation method of macromolecular keratin-PVA gel is the same as the preparation steps of Example 1, except that NaCl is not added, and comprises the following steps:
[0094] S1. Wash and chop 20g of white-feather chicken feathers, add them to 1L of keratin extract containing 15g of L-cysteine, microwave them for 10min at a microwave power of 400W and a temperature of 90°C, pour them into a dialysis bag and dialyze them with deionized water for three days. The molecular weight cutoff of the dialysis bag is 8K-14KDa to obtain a pure keratin solution.
[0095] S2. Use 1 mol / L HCl solution to adjust the pH of 10 mg / mL keratin solution to 2.0, heat it in a water bath at 90° C. for 6 h, obtain keratin aggregates, freeze-dry them, and set aside.
[0096] S3. Mix the keratin aggregates in water, and adjust the pH to 7.2 with a 2 mol / L NaOH solution to obtain a keratin aggregate solution with a mass percentage of 5 wt%.
[0097] S4. PVA was mixed with water, and stirred in a 90° C. water bath for 3 h to ensure that the PVA was fully dissolved, thereby obtaining a PVA solution with a mass percentage of 30 wt %.
[0098] S5. After mixing the keratin aggregate solution and the PVA solution, stir at 50° C. for 3 h to make the mass percentage of keratin aggregates in the system be 2 wt %, and the mass percentage of PVA be 15 wt %, to obtain a PVA-keratin mixed solution.
[0099] S6. The PVA-keratin mixed solution was first frozen at -20°C for 22 hours, and then thawed at 25°C for 2 hours. The freezing and thawing cycles were repeated three times to obtain a macromolecular keratin-PVA gel, which was recorded as HK or 2% K.
[0100] Comparative Example 2
[0101] The preparation steps are the same as those of Comparative Example 1, except that the mass percentage of keratin aggregates is replaced by 1 wt %, which is 2 wt %, and is recorded as 1%K.
[0102] Comparative Example 3
[0103] The preparation steps are the same as those of Comparative Example 1, except that the mass percentage of keratin aggregates is replaced by 3wt% (2wt%), which is recorded as 3%K.
[0104] Comparative Example 4
[0105] The preparation steps are the same as those of Comparative Example 1, except that the mass percentage of keratin aggregates is replaced by 4wt% (4%K), which is 2wt%.
[0106] Comparative Example 5
[0107] The preparation method of PVA gel comprises the following steps:
[0108] PVA was mixed with water and stirred in a 90°C water bath for 3 h to ensure that PVA was fully dissolved to obtain a PVA solution with a mass percentage of 15 wt%. The PVA solution was then frozen at -20°C for 22 h and then thawed at 25°C for 2 h. The freeze-thaw cycle was repeated 3 times to obtain a PVA gel, which was recorded as PVA.
[0109] Comparative Example 6
[0110] The preparation method of hydrolyzed keratin-PVA gel comprises the following steps:
[0111] S1. Mix hydrolyzed keratin (whose molecular weight is less than 2 KDa) in water, and adjust the pH to 7.2 with a 2 mol / L NaOH solution to obtain keratin aggregates with a mass percentage of 5 wt%.
[0112] S2. PVA was mixed with water and stirred in a 90° C. water bath for 3 h to ensure that the PVA was fully dissolved, thereby obtaining a PVA solution with a mass percentage of 30 wt %.
[0113] S3. After mixing the keratin aggregate solution and the PVA solution, stir at 50° C. for 3 h to make the mass percentage of keratin aggregates in the system be 2 wt %, and the mass percentage of PVA be 15 wt %, to obtain a PVA-keratin mixed solution.
[0114] S4. The PVA-keratin mixed solution was first frozen at -20°C for 22 hours, and then thawed at 25°C for 2 hours. The freezing and thawing cycles were repeated three times to obtain a hydrolyzed keratin-PVA gel, which was recorded as HyK.
[0115] Comparative Example 7
[0116] The preparation method of polyvinyl alcohol-keratin semi-interpenetrating network hydrogel is the same as the preparation steps of Example 5, except that Ca 2+ Replaced from 2 mol / L to 3 mol / L, the amount of ion added is 0.15 mol / L, recorded as 0.15Ca or 0.15C.
[0117] Comparative Example 8
[0118] The preparation method of polyvinyl alcohol-keratin semi-interpenetrating network hydrogel is the same as the preparation steps of Example 5, except that Ca 2+ Replaced from 2 mol / L to 4 mol / L, the amount of ion added is 0.2 mol / L, recorded as 0.2Ca or 0.2C.
[0119] Examples 1-9 of the present invention all prepared polyvinyl alcohol-keratin semi-interpenetrating network hydrogels with excellent mechanical properties, strong moisture control ability, and physical and chemical stability. The polyvinyl alcohol-keratin semi-interpenetrating network hydrogels of Examples 1-7 are taken as examples and compared with Comparative Examples 1-8. The specific research methods and results are as follows:
[0120] Figure 1 The SEM imaging results show that PVA forms pores during the freeze-thaw process, and after adding hydrolyzed keratin or macromolecular keratin, the network structure is more compact and the uniformity of the pores is improved. In addition, EDS analysis shows that Na + , Ca 2+ and Al 3+ Successfully embedded in the gel, the increase in cation concentration changed the interaction between the macromolecular keratin-PVA gel and affected its stability.
[0121] The rheological properties of the gel were tested as follows:
[0122] S1. The rheological properties of the gel were tested using a rheometer (MCR301, Anton Parr, Austria), and the probe was PP50.
[0123] S2, frequency sweep: the temperature is set to 25 ° C, in order to determine the apparent viscosity, the shear rate is 1-100s -1 The storage modulus (G′) and loss modulus (G″) were measured in the range of 0.1% strain and the frequency sweep (0.1-10 Hz) was performed at 0.1% strain.
[0124] S3. Use the power law equation to model the frequency sweep results. The formula is: G'=K'ω n′ , where G′ is the storage modulus (Pa), K′ is the consistency coefficient (Pa·sn), ω is the angular frequency (rad / s), and n′ is the flow behavior index.
[0125] Figure 2 The results in Figure A show that when the concentration of macromolecular keratin increases, the G' value of the gel increases with the increase in the concentration of macromolecular keratin. The addition of 2% and 3% has no significant effect on the elasticity of the macromolecular keratin-PVA gel, but the addition of 4% macromolecular keratin leads to an increase in the elastic part of the hydrogel. Figure 2 D The results show that tan(δ) generally increases with the increase of macromolecular keratin concentration, which indicates that the hydrogels with higher macromolecular keratin concentration are more viscous and relatively less elastic.
[0126] Figure 2The results in Figure B show that after adding sodium ions, the G' of the gel first increases and then decreases with the increase of ion concentration, reaching the maximum value of G' at an addition amount of 0.15 mol / L. G" has a similar trend. This may be because the low concentration of sodium ions reduces the electrostatic repulsion between polymer chains, promotes the interaction between chains, and thus increases the cross-linking sites. Figure 2 The results showed that hydrogels with higher sodium ion concentrations exhibited higher viscosity, and when the sodium ion concentration exceeded 0.15 mol / L, the effect of sodium ions on the viscoelasticity of the gel tended to saturation.
[0127] Figure 2 The results in C show that the addition of calcium ions will significantly reduce the G' value of the gel. When it exceeds 0.15 mol / L, the gel will not form. This may be because excessive calcium ions cause excessive cross-linking of the gel and even form a granular network, thus affecting the viscoelasticity of the gel. Figure 2 The results in Figure 5 show that when the calcium ion concentration increased from 0.05 mol / L to 0.2 mol / L, tan(δ) generally increased, indicating that calcium ions also increase the viscosity of the hydrogel.
[0128] The G results in 2 show that the frequency scanning results of the three groups of gels were fitted with a power law equation. The increase in keratin concentration also enhanced the rigidity of the gel. An appropriate amount of keratin can improve the gel properties, but excessive addition may lead to a decrease in performance.
[0129] In summary, when rheological frequency scanning analysis was performed on the modulus changes of different gels, the elastic modulus (G') of the gel increased significantly with the increase of keratin concentration, especially when the addition amount was 4%, it showed stronger gelling properties. In addition, the addition of sodium ions and calcium ions had different effects on the gel modulus: low concentrations of sodium ions helped to increase the cross-linking sites, but high concentrations led to a decrease in gel hardness; excessive addition of calcium ions significantly reduced the strength and stability of the gel.
[0130] The mechanical properties of the gel were tested as follows:
[0131] S1. Use a knife to modify the gel size into a 10 mm × 10 mm × 15 mm square.
[0132] S2. Compress the probe (P / 36R) to 50% of its original height. The test mode is TPA. The speeds before, during and after the test are 1mm / s, 5mm / s and 5mm / s respectively. The trigger force is 5g.
[0133] Figure 3 The results show that with the increase of keratin addition, the hardness of the gel increased significantly, reaching 337.218 g, which is mainly due to the combination of keratin hydroxyl groups and PVA to enhance the mechanical properties and stability of the gel. +After that, the gel hardness dropped significantly to 64.668 g, which may be due to Na + The hydrogen bonding interaction between PVA and keratin was disturbed, resulting in a loose gel structure and a significant reduction in mechanical properties. 2+ The introduction of also led to a decrease in the hardness of the gel, especially at high concentrations, the gel even became shapeless, which indicated that the charge shielding effect and the degree of destruction of weak interactions aggravated the structural instability of the gel.
[0134] Test the water absorption of gel as follows:
[0135] S1. Dry the gel to a constant weight.
[0136] S2. Immerse the sample in a 37°C PBS solution (pH 7.4), and then weigh it at 0h, 3h, 6h, 9h, 12h, 24h and 48h after immersion.
[0137] S3. Calculate the expansion rate (SD), the formula is: SD = (m i -m0) / m0×100%, m0 represents the mass of dry hydrogel, m i is the mass of the hydrogel at a specific time after swelling (g).
[0138] Figure 4 The results show that the water absorption is in the order of PVA>HyK>NaK>CaK>HK. PVA has the highest water absorption because its hydroxyl groups can form hydrogen bonds with water molecules; HyK slightly increases the density but still maintains good water absorption, while HK significantly reduces the water absorption, mainly due to its strong interaction to enhance the network density. The water absorption of NaK and CaK is lower than that of PVA and HyK, but higher than that of HK, and the calcium bridge structure of calcium ions further reduces the water absorption.
[0139] The thermal stability of the gel was tested according to the following method: after the gel was freeze-dried, the temperature rate was 10°C / min and the thermogravimetry was measured between 30°C and 300°C.
[0140] Figure 5 The results showed that the temperature of the first peak in HK shifted to a higher position, which may be due to the hydrogen bonds formed between keratin and PVA, which enhanced the thermal stability of the gel. + and Ca 2+ The addition of Al 3+ The addition of resulted in the merging of the double peaks into one characteristic peak, indicating that its strong cross-linking effect may have affected the structure and thermal properties of the gel.
[0141] Test the distribution of water molecules in the gel according to the following method:
[0142] S1. Use a knife to modify the gel size into a 10 mm × 10 mm × 15 mm square.
[0143] S2. The samples were placed in NMR tubes and analyzed in five parallel runs at 26 °C, spin relaxation time (T2) was measured, and a CPMG sequence was used with an echo time of 0.5 ms, 2500 echoes, and 8 scans.
[0144] Figure 6 The results showed that LF-NMR analysis showed that the interaction between water molecules and the gel network increased with the increase of keratin concentration, while high concentration of Na + and Ca 2+ It will cause the water distribution to rearrange and reduce the hardness and stability of the gel. As the keratin concentration increases, the proportion of bound water first increases and then decreases, reaching the highest when 2% keratin is added, while Na + As the concentration increases, the proportion of bound water continues to rise. 2+ After addition, although the proportion of non-mobile water was high, the gel network was too loose due to peak fusion, affecting its stability.
[0145] The molecular structure of the gel was tested as follows:
[0146] S1. Freeze-dry the gel.
[0147] S2, using 785nm diode laser as excitation source, at 3400-50cm -1 The extended spectra were collected within the range and averaged over at least 10 accumulations, with each exposure time being 20 s.
[0148] Figure 7 The results show that the addition of ions leads to defect peaks in the gel sample, while the addition of only hydrolyzed keratin or keratin macromolecules does not have an adverse effect on the PVA gel system. The destructive effect of calcium ions is stronger than that of sodium ions, while aluminum ions significantly weaken the interaction between molecules, resulting in a fragile internal structure of the sample. The presence of calcium ions significantly increases the disordered peak, indicating that it is more destructive to the gel structure than sodium ions, which may be related to the strong cross-linking effect of calcium ions in the network. In contrast, the introduction of aluminum ions reduces all Raman peaks, showing that it severely damages the interaction between PVA and keratin molecules, which may lead to a weakening of intermolecular forces, thereby affecting the overall stability and performance of the gel.
[0149] Gel crystallography information was tested as follows:
[0150] S1. Freeze-dry the gel.
[0151] The S2 X-ray source used Cu-Kα radiation at 40 kV and 40 mA, and data were collected at a rate of 8° / min in the scattering angle range of 5°-85°.
[0152] Figure 8 The results showed that the width and low intensity of the characteristic response peak in the gel formed after three freeze-thaw cycles of PVA indicated that its crystallinity was poor. With the introduction of hydrolyzed keratin and macromolecular keratin, the sample showed significant high response characteristic peaks at 35° and 45°, indicating that keratin changed the crystal structure of the gel by enhancing the interaction with PVA, forming new crystallization areas and significantly improving the crystallinity of the hydrogel.
[0153] Test the gel molecular alignment as follows:
[0154] S1. Freeze-dry the gel.
[0155] S2. The X-ray wavelength is set to 0.154 nm and the scattering image is subjected to circular averaging to obtain a scattering curve as a function of the wave vector q.
[0156] S3. Use the Beaucage equation to analyze and fit the low-q region of the image. The equation is:
[0157]
[0158] Among them, G and G s are the Guinier pre-factors of the larger and smaller structures, R g is the radius of gyration, R s is the minimum R observed at high q g , while R sub In the high q limit, B and B s are prefactors specific to power-law scattering, specified as decay exponents P and P, respectively. s , q*=q / [erf(qkR g / 6 1 / 2 )] 3 andq s * = q / [erf(qk s R s / 6 1 / 2 )] 3 .
[0159] Fig. 9The results showed that PVA in all gels formed a lamellar structure, and pure PVA showed the highest scattering intensity, indicating that its nanostructure was the most ordered. Although the addition of keratin enhanced the compactness of the gel, the steric hindrance effect of macromolecular keratin caused the scattering intensity of the HK group to decrease, and the hydrolyzed keratin reduced the order of HyK due to its small molecular weight. In contrast, NaK had the highest scattering intensity, indicating that sodium ions promoted the ordered structure at the nanoscale.
[0160] Through Fig.10 The Beaucage unified model was fitted to the power law behavior region of the SAXS curve, and the results showed that PVA had the highest scattering intensity and density, indicating that its internal structure was relatively ordered. NaK and HK also retained a large nanostructure, while HyK showed a relatively loose internal structure. In contrast, CaK and AlK had lower scattering intensities, reflecting a rougher and irregular internal structure, which is consistent with the looseness caused by strong cross-linking.
[0161] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalent technologies, the present invention is also intended to include these changes and variations. The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and their protection scope is not limited thereto. Equivalent substitutions or changes made by those skilled in the art on the basis of the present invention are all within the protection scope of the present invention, and the protection scope of the present invention shall be subject to the claims.
Claims
1. A method for preparing a polyvinyl alcohol-keratin semi-interpenetrating network hydrogel, characterized in that: The steps include: Using keratin with a molecular weight greater than 2 kDa as a raw material, mixing an aqueous solution of keratin aggregates with an aqueous solution of polyvinyl alcohol, and then adding a metal salt to obtain a PVA-keratin mixed solution; Wherein, the metal salt is selected from soluble sodium salt, soluble calcium salt or soluble aluminum salt; when the metal salt is selected from soluble sodium salt, the concentration of soluble sodium salt in the PVA-keratin mixed solution is 0<c≤0.2mol / L, when the metal salt is selected from soluble calcium salt, the concentration of soluble calcium salt in the PVA-keratin mixed solution is 0<c≤0.1mol / L, when the metal salt is selected from soluble aluminum salt, the concentration of soluble aluminum salt in the PVA-keratin mixed solution is 0<c≤0.1mol / L; The PVA-keratin mixed solution is frozen and thawed to allow the polyvinyl alcohol to form a network gel structure, and the metal ions of the metal salt are used to interact with the functional groups in the PVA-keratin mixed solution to produce electrostatic shielding, ion bridge effect or charge induction effect to obtain the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel.
2. The method for preparing the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel according to claim 1, characterized in that: The keratin is selected from feather keratin or wool keratin.
3. The method for preparing the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel according to claim 1, characterized in that: In the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel, the mass percentage of keratin aggregates is 1wt% to 4wt%.
4. The method for preparing the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel according to claim 1, characterized in that: In the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel, the mass percentage of polyvinyl alcohol is 14wt%-16wt%.
5. The method for preparing the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel according to claim 1, characterized in that: First freeze at -18℃~-22℃ for 22h, then thaw at 20℃~30℃ for 2h.
6. The method for preparing the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel according to claim 1, characterized in that: Microwave-assisted L-cysteine method was used to extract keratin from hair.
7. A polyvinyl alcohol-keratin semi-interpenetrating network hydrogel prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel according to claim 7 in the preparation of biomedical materials.
9. Use of the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel according to claim 7 in preparing food packaging materials.
10. Use of the polyvinyl alcohol-keratin semi-interpenetrating network hydrogel according to claim 7 in preparing flexible electronic components.
Citation Information
Patent Citations
Method for regulating nerve cell growth by using polyvinyl alcohol / silk fibroin hydrogel
CN109266608A
Hydrogel cell scaffold and preparation method thereof
CN111437435A
Freeze-thaw hydrogel of polyvinyl alcohol and producing method thereof
JP2024144112A
Method of manufacturing hydrogels used in wound closures
KR1020140122151A
Cited By
Double-layer structure sensor for robot skin as well as preparation method and application of double-layer structure sensor
CN122016100A